The contested rewe: sacred sites, misunderstandings, and ontological pluralism in Mapuche land negotiations - Di Giminiani, Piergiorgio (The Journal of the Royal Anthropological Institute, 2013)
Sacred sites lie at the core of indigenous peoples' land claims and negotiations with the state. These sites are often subject to accusations of inauthenticity by state actors, which potentially lead to the delegitimization of claims over ancestral land. This article argues that misunderstandings in Mapuche land negotiations in Chile do not originate as strategic refusals to understand, but rather in a form of understanding which aims to make radical differences commensurable within the logics of statecraft and national society. In the process of cultural translation, the ontological principles that make certain places sacred in the Mapuche lived world are not recognized, resulting in the transformation of these sites into symbols of identity strategically employed for political ends. Les sites sacrés sont au coeur des revendications et négociations des peuples autochtones avec les gouvernements. Les pouvoirs publics mettent souvent en doute l'authenticité de ces sites, ce qui peut délégitimer les droits invoqués sur les terres des ancêtres. L'auteur affirme ici que les malentendus liés aux négociations sur les terres des Mapuche au Chili ne sont pas nés d'un refus stratégique de comprendre mais d'une forme de compréhension qui tente de rendre des différences radicales compatibles avec la logique du pouvoir public et de la société nationale. La transition culturelle ne reconnaît pas les principes ontologiques qui rendent certains sites sacrés dans le monde vécu par les Mapuche, sites qui se trouvent de ce fait transformés en symboles d'identité et employés stratégiquement à des fins politiques.